Idiomatic Expressions and Semiotic Analysis on Marvel's Avengers: Endgame (2019) Movie - Retno Ramadhina; Rina Husnaini Febriyanti; Neni Nurkhamidah (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2026)
The purpose of this research is to find out the idiomatic expressions and semiotic cues shown in Marvel’s Avengers: Endgame (2019) Movie as final one to conclude all the movies on the Infinity Saga. This Saga consist of twenty-three movies started from Iron Man in 2008 until Avengers: Endgame in 2019. This research employs qualitative descriptive method while sociolinguistics and semiotic are used as the approaches. The movies’ scenes and dialogues are used as the primary data while scientific articles, books, and popular articles as secondary data. The data will be analyzed by reducing, displaying, and concluding them into the suitable categories and being explained. The researchers use McCarty and O’Dell’s theory of idioms and Peirce’s theory of signs for the data analysis. By doing this research, it is found that many kinds of idiomatic expressions like similes, binomials, proverbs, etc. can be found on the movies so that it will be easier for the readers to understand the usage of idiomatic expressions in any form of context. It is also hope that by identifying the messages signed by the symbols shown on the movies, the readers can be inspired and refer to societal reality. This research may contribute to a wider understanding and implementation of idiomatic expressions usage in any context and trigger readers critical thinking in identifying messages shown in signs or texts.